Kompos solusi alami untuk pertanian berkelanjutan dan lingkungan yang lebih sehat - azizah, yunifa yunifa (Maliki Interdisciplinary Journal, 2025)
Composting is a sustainable solution for managing organic waste and improving agricultural soil quality. This article discusses the benefits, processes, and challenges of composting at both household and industrial levels. The study reveals that composting can reduce waste ending up in landfills, decrease greenhouse gas emissions, and significantly enhance land productivity. However, the implementation of composting faces obstacles such as low public awareness, limited space, and inadequate infrastructure support. This review suggests increased collaboration among the government, communities, and the private sector to promote compost adoption as part of a sustainable agricultural solution. Furthermore, this study highlights the importance of education and outreach regarding organic waste management as a first step in building environmental awareness at the grassroots level. Participatory approaches through training and community mentoring have proven effective in improving residents’ ability to process organic waste into high-value compost and eco-enzymes. Simple technological innovations, such as closed composting systems and the use of natural bioactivators, can also accelerate the decomposition process and improve the quality of the resulting compost. Thus, implementing an integrated organic waste management strategy not only contributes to waste reduction and environmental preservation but also opens up opportunities for a circular economy in agriculture and sustainable resource management.